2022
DOI: 10.1177/14034948221074974
|View full text |Cite
|
Sign up to set email alerts
|

Effects of rehabilitative psychotherapy on labour market success: Evaluation of a nationwide programme

Abstract: Aims: Psychotherapy is a widely used treatment for mental disorders, but whether it also improves employment and other labour market outcomes remains inconclusive. This study examined the effectiveness of a nationwide subsidized psychotherapy programme using extensive register-based data. Methods: The sample consisted of individuals who applied for rehabilitative psychotherapy in Finland in 2009–2012 ( n = 35,083). Prior to 2011, some applications were rejected due to the limited budget that the central govern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…We found that participating in rehabilitative psychotherapy marked a decline in depression-related or anxiety-related work disability in comparison to the counterfactual trend. Our findings are in accordance with a recent Finnish register-based longitudinal study, 26 which found that rehabilitative psychotherapy was associated with an improvement in the employment and other labour market outcomes of the recipients of rehabilitative psychotherapy. Our findings are also in agreement with those of studies reporting the beneficial effects of psychotherapy on depression and anxiety.…”
Section: Discussionsupporting
confidence: 92%
“…We found that participating in rehabilitative psychotherapy marked a decline in depression-related or anxiety-related work disability in comparison to the counterfactual trend. Our findings are in accordance with a recent Finnish register-based longitudinal study, 26 which found that rehabilitative psychotherapy was associated with an improvement in the employment and other labour market outcomes of the recipients of rehabilitative psychotherapy. Our findings are also in agreement with those of studies reporting the beneficial effects of psychotherapy on depression and anxiety.…”
Section: Discussionsupporting
confidence: 92%
“…Evidence suggests that, at a population level, long-term psychotherapy might be linked to decreased work disability. [15][16][17] However, a more detailed analysis has revealed that among individuals who were granted a disability pension, 11-60 psychotherapy sessions were associated with a partial or full return to work, whereas longer psychotherapies did not. 18 In addition, some evidence suggests that short-term therapies are linked with quicker improvement in workability, while long-term psychotherapy offers more enduring gains.…”
Section: Introductionmentioning
confidence: 99%
“…Implementing these findings to community‐based samples, with greater population diversity and varying psychotherapy durations, is not straightforward. Evidence suggests that, at a population level, long‐term psychotherapy might be linked to decreased work disability 15–17 . However, a more detailed analysis has revealed that among individuals who were granted a disability pension, 11–60 psychotherapy sessions were associated with a partial or full return to work, whereas longer psychotherapies did not 18 .…”
Section: Introductionmentioning
confidence: 99%
“…After the referral, a patient needs to find an available psychotherapist from the private healthcare sector. Results from two recent studies suggest that rehabilitation was associated with somewhat better labor market outcomes [ 31 , 32 ]. However, there is no information on whether occupational status or area of residence influence work disability progress during and after rehabilitation and to what extent disability trajectories have differed among individuals who started rehabilitative psychotherapy after it became accessible to all eligible for the benefit.…”
Section: Introductionmentioning
confidence: 99%